1995
DOI: 10.2307/1938148
|View full text |Cite
|
Sign up to set email alerts
|

Predation as an Agent of Population Fragmentation in a Tropical Watershed

Abstract: Stream fish sometimes show mutimodal distributions, with high densities in the tributaries of a river but rarity or absence in the river itself. To assess if predation can produce such a fragmented distributional pattern on a large geographic scale, we determined the density and habitat use of a prey fish in two tropical stream watersheds, each with a barrier waterfall that split the drainage into a region with a strongly piscivorous fish and a region lacking a strong lacking a strong piscivore. In contrast to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
121
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(128 citation statements)
references
References 25 publications
(26 reference statements)
7
121
0
Order By: Relevance
“…The opposite pattern, albeit less documented, is also possible: there may be a stabilizing effect of predators on population dynamics [19] or 'hydra effects' [31], whereby predation increases average prey population density, potentially decreasing the extinction rate and/or increasing the colonization rate. Non-consumptive effects can also have contrasting impacts: colonization and extinction rates may increase owing to emigration from high-risk patches [32], but colonization may also decrease because of increased vigilance and/or decreased activity levels [33].…”
Section: Results (A) Perturbation-versus Extinction-limited Chainsmentioning
confidence: 99%
“…The opposite pattern, albeit less documented, is also possible: there may be a stabilizing effect of predators on population dynamics [19] or 'hydra effects' [31], whereby predation increases average prey population density, potentially decreasing the extinction rate and/or increasing the colonization rate. Non-consumptive effects can also have contrasting impacts: colonization and extinction rates may increase owing to emigration from high-risk patches [32], but colonization may also decrease because of increased vigilance and/or decreased activity levels [33].…”
Section: Results (A) Perturbation-versus Extinction-limited Chainsmentioning
confidence: 99%
“…She found that the effect of fish predation on benthic macroinvertebrates was dependent on season and habitat complexity. However, Fraser et al (1995) performed both inclusion and exclusion experiments in streams on the tropical island of Trinidad and found that in areas split by barrier waterfalls, predators can produce disjointed prey distributional patterns, by both consumption and by causing prey to ascend cascades. In addition, Reznick et al (1997) moved guppies from pools with many predators below barrier waterfalls into pools with only one predator above waterfalls in Trinidadian rivers.…”
Section: Discussionmentioning
confidence: 99%
“…thereby reducing the number of individuals available to disperse; 2) non-consumptive effects, whereby predators increase or decrease rates of prey flux by influencing prey movement (i.e., changing the likelihood that an individual will disperse or the mean phenotype of dispersers). For example, the dynamics of fish populations (prey) in predator-free tributaries are a function of predators in connecting streams not only because consumption by predatory fish reduces dispersal of smaller fish (Fraser et al 1995), but also because surviving prey are more likely to disperse from areas that contain predators (Fraser et al 1999, Gilliam and. Non-consumptive remote effects also arise when mobile prey choose to avoid otherwise suitable habitats that contain predators (e.g., Kats and Sih 1992, Resetarits 2001, Resetarits 2005, Resetarits and Binckley 2009).…”
Section: What Are Remote Effects?mentioning
confidence: 99%